PENGARUH SIANIDA PADA FOTOREDUKSI Hg(II) YANG DIKATALISIS TiO2 - Diky Hidayat (Molekul, 2011)
Influence of cyanide on the photoreduction of Hg(II) catalyzed by TiO2 had been studied. Photoreduction process was carried out in a closed reactor equipped with UV lamp The process was done by radiated and stirred a mixture of Hg(II) solution, TiO2, and cyanide for a certain period of time. The amount of reduced Hg(II) by photoreduction was calculated by the substracting initial Hg(II) concentration with unreduced one, which was determined by usedcold vapor atomic absorption spectrophotometer method. In this research influences of solution concentration and pH solution in the presence cyanide were also evaluated.The result of this research indicated that the presence of cyanide lead to decrease Hg(II) photoreduction, and a drastical drop was observed when more than 2 mmole cyanide was added for each mmole of Hg(II). Increased pH solution from 2 to 4 in the presence of cyanide can improve photoreduction process, but further increased of pH solution higher than 4 lead to decrease photoreduction of Hg(II).